Improving Teacher Professionality Through CPD at State Madrasah Aliyah & Private Madrasah Aliyah In Sibolga City and Central Tapanuli District - Oktaviana Mekawati, Nurul; Wijaya, Candra; Masganti, Masganti (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to determine the professional competence of teachers, forms of teacher coaching, the implementation of continuous professional development for teachers, and the influence of continuous professional development in the form of self-development, scientific publications, and innovative work which have a positive effect on increasing the professional competence of MAN and MAS teachers in Sibolga and Regency. Central Tapanuli. The method used in this research is qualitative using a PAR (Participatory Action Research) approach and quantitative using path analysis. The research sample amounted to 217 people. The research results in this dissertation show that teacher professionalism in MAN and MAS Sibolga City and Central Tapanuli Regency still faces various challenges that affect the quality of education, such as lack of learning planning, use of innovative media, as well as weaknesses in material mastery and evaluation. Factors such as low discipline and lack of continuous training are significant obstacles, which can be overcome through supervision of madrasa heads and improving infrastructure. The Continuous Professional Development Program (PKB) plays an important role in increasing teacher competency, even though it faces challenges of limited resources and infrastructure support. The implementation of FGDs on professionalism and CPD showed an increase in teacher participation and teaching quality, in line with professional development theory. Various indicators, such as the ability to plan learning, use of technology, creativity, and involvement in collective activities and scientific publications, interact with each other to form better teacher professionalism. The synergy between individual competency development and effective educational management is very important in improving the quality of education and student learning outcomes in the region.